Sartans: differences, similitudes and costs - Zaniolo, Orietta; Iannazzo, Sergio (Farmeconomia. Health economics and therapeutic pathways, 2008)
The search for a more specific and complete blockade of the hypertensive effects of angiotensin and of better tolerability than ACE-inhibitors has led to the development of angiotensin II receptor blockers (ARBs), which were introduced about 10 years ago. During this period they have been evaluated in several large studies in terms of efficacy and safety in reducing blood pressure, as well as for cardiovascular and renal protection. In patients with heart failure, valsartan, candesartan and, partially, losartan have been shown to be associated with positive outcomes both as monotherapy, when ACE-inhibitors are contraindicated or not tolerated, and in combination with ACE-inhibitors standard therapy. Among ARBs, valsartan is the only that is also approved for treatment of patients with both heart failure and recent myocardial infarction. In light of the high costs related to cardiovascular disorders, agents that reduce cardiovascular risk, like ARBs, represent a potential long-term health cost saving strategy, if used according to guidelines in approved indications. Valsartan has a daily cost which is lower than the mean cost of the class. Furthermore, this drug shows one of the lowest costs for patient brought to blood pressure goals in its class. In this paper, economic evaluations conducted on the results of large trials were reviewed. Their results add economic rationale to the therapeutic algorithms recommended by clinical guidelines on heart failure management; using valsartan, or other evaluated ARBs, in heart failure patients who are intolerant or contraindicated to ACE-inhibitors therapy, is expected to be highly cost/effective. In combination with ACE-inhibitors in those patients not on beta-blocker therapy, its cost/effectiveness is somewhat worse, but still acceptable, with an estimated cost of 15,000 USDs for life year saved. In summary, when used for approved indications, valsartan offers attractive economic features for the healthcare provider and has a positive impact on the cardiovascular morbidity and health-related quality of life of these patient populations.